RANCANGAN OPERASI KESEHATAN DAN KESELAMATAN KERJA DENGAN PENDEKATAN 5M DI LINGKUNGAN PRODUKSI BENANG DI MASA COVID-19 PT.IPCI - Darmawan Yudhanegara; Agus Ahmad Kosim; Muhammad Ihsan; Pandena Kicky Basuki Putri (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
Production at that time was carried out with the company's needs, even during a pandemic, it was necessary to carry out operations that were optimally applied in production. The 5M model (wearing masks, washing hands, maintaining distance, avoiding crowds and limiting mobility) to be implemented in Production is quite difficult, so it needs a special design that describes operations that maintain health in conditions of continuous production. The habit of workers who carry out activities that violate the process is considered a must to do, even though these activities have the potential to spread the virus. Lack of awareness of workers who do not pay too much attention to calls to implement health protocols.